Optimalisasi Potensi Udang Lokal dalam Pembuatan Produk Kerupuk Udang di Desa Punti Kabupaten Bima - Yusnia Ayusari; Husnul Khotimah; Nurul Hidayanti; Wahyu Ramadhan; Sahrul Sahrul; Febi Berliana; Aida Zulwahidah; Ismunandar Ismunandar; Muhammad Badar (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2025)
Punti Village, Soromandi District, Bima Regency, has significant local shrimp potential, but it has not been fully utilized for the development of value-added products. The MBKM Thematic Community Service Program (KKN) plays a key role in optimizing this potential by processing shrimp into shrimp cracker products. Using a participatory approach, KKN students collaborated with the local community in various stages of shrimp cracker production, including raw material selection, production processes, and marketing. The results of this program indicate that optimizing local shrimp potential enhances community skills in shrimp cracker production and creates opportunities for increased income. The conclusion of this activity is that optimizing local shrimp potential through the KKN program has a positive impact on local economic empowerment and improves the welfare of the community.